CAPACITIVE RESISTIVITY METHOD APPLIED TO THE ENVIRONMENTAL DIAGNOSIS AND MANAGEMENT OF CONTAMINATED AREA OF GAS STATION - Aquino, Wagner França [UNESP]; da Silva, Marcio Corrêa; Tonello, Paulo Sergio [UNESP] (Sociedade Brasileira de Geofisica, 2022)
This article presents a case study of fuel underground contamination where the geophysical method was applied to support for decision making regarding environmental management activities. The application of geophysical methods that measure electrical resistivity in the study of contaminated areas and their correlations with organic contaminants are discussed, in addition to the presentation of theoretical and practical aspects of Capacitive Resistivity (CR) method. The importance of this work is based on the evaluation of the potential for identification of free phase of organic contaminant by the capacitive method and the assessment of the effectiveness of the remediation implemented through the geophysical data obtained. The method applied was able to identify the highest electrical resistivities related to fuel in the subsurface and indicated the inefficiency of the current remediation by the inadequate positioning of the extraction wells and the inaccuracies in the monitoring of underground contamination and allowed the proposition of recommendations related to management of the case based on geophysical information. From results, it is concluded that the Capacitive Resistivity method can be applied in similar cases of leaks in gas stations to diagnose contamination and to guide the adoption of more appropriate actions of environmental management.
Keywords: contaminated soils; electrical resistivity; organic contaminants